Effects of a whole body vibrating platform on postural balance in elderly persons - Silva, Patrícia Zambone da; Schneider, Rodolfo Herberto (Acta Fisiátrica, 2011)
The aging process causes several physiologic changes such as, muscle mass loss, and a decrease in balance and postural control. As a consequence of these transformations, the risk of falls increases, an important event that can signal the beginning of decline in an elderly person’s health. Several approaches have been used for fall prevention, the most recent of these is the use of a whole body vibration platform that has been shown to improve balance and postural control in the elderly, therefore decreasing the risk of falls and their after effects. This literature review focuses on the most relevant articles about this subject. The obtained results showed an improvement in balance and postural control in this population when compared with exercising, physiotherapy or sedentarism. Nevertheless, there are many different training protocols, making it difficult to compare the results. This review demonstrates that whole body vibration is a promising intervention for fall prevention in the elderly, however more research is necessary to determine the most suitable treatment protocol for improving balance.